Analisis Isi Pesan Dakwah Pada Akun YouTube @Culapculip - Putri Indriyani; Tomi Hendra (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2023)
Culapculip is a YouTube account founded by Cak Sugik, which contains Islamic teachings. In today's modern era, many people think that preaching is only from pulpit to pulpit. Even though with the sophistication of technology, nowadays preaching can be done anywhere and only need to post it on social media, for example YouTube. This study uses a qualitative method with a descriptive approach. Data collection is done by observation and documentation. Based on the results of the research, the content of da'wah messages on the YouTube video @culapculip for the period August 2021 resulted in findings, as much as two video included the aspect of faith, where in this aspect the da'wah video was more inclined to discuss belief in Allah SWT and the Prophet Muhammad SAW. Then, as much as 8 video goes into sharia aspects, in this aspect it is more likely to discuss worship performed to Allah SWT. Furthermore, the two videos go into the moral aspect, which in this aspect is more likely to discuss a person's behavior and actions.